Adrenal Crisis in a Patient with Addison's Disease: A Case Report and Review of the Condition in Our Part of the Country, Nepal (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Addison's disease, also known as Primary Adrenal Insufficiency, is a rare endocrine disorder characterized by inadequate production of cortisol, aldosterone, and androgen by the adrenal glands. Adrenal crisis, a life-threatening complication of Addison's disease, occurs when the body cannot produce sufficient glucocorticoids to meet physical or emotional stress. This case report presents a 60-year-old female with Addison's disease who developed adrenal crisis due to acute gastroenteritis. The patient presented with non-specific symptoms of nausea, vomiting, lethargy, and abdominal pain, which were initially attributed to gastroenteritis. However, further evaluation revealed hyponatremia, hyperkalemia, and anemia, leading to the diagnosis of adrenal crisis. The patient was managed with intravenous hydrocortisone, fluid resuscitation, and antibiotics, and recovered after two days of hospitalization. This case highlights the importance of prompt diagnosis and management of adrenal crisis, which can be precipitated by infections, including gastroenteritis. The report also reviews the different aspects of adrenal crisis and Addison's disease in our part of the country, emphasizing the need for increased awareness, education, and preventive measures to reduce morbidity and mortality associated with these conditions.